Albumin: a mediator of the association between serum calcium and triglyceride-glucose index among Chinese individuals with osteoporotic fractures - Liang, Jia-qi; Xu, Jian; Cao, Yan; Wei, Yin-lin; Lin, Guo-ji; Jin, Jian; Li, Chong; Lu, Ke (Frontiers in Endocrinology, 2025)
BackgroundOsteoporotic fractures (OPFs) are a major global health concern, affecting nearly 200 million individuals worldwide. Notably, patients with type 2 diabetes mellitus (T2DM) face a heightened fracture risk, even when bone mineral density (BMD) is normal or elevated. This study investigated the associations between serum calcium (Ca), triglyceride-glucose (TyG) index, albumin, and their interactions in Chinese patients with OPFs.MethodsThis cross-sectional study included 1,541 participants who were 50 years of age or older, recruited from the Affiliated Kunshan Hospital of Jiangsu University between January 2017 and August 2023. The primary independent and dependent variables were serum Ca and the TyG index, respectively. Albumin served as the mediating factor in this analysis. The relationship between serum Ca or albumin and the TyG index was investigated using multivariable logistic regression analyses. A mediation analysis was conducted to ascertain whether albumin mediated the relationship between serum Ca and the TyG index.ResultsThe study revealed a positive correlation between serum Ca and TyG index, with each unit increase in serum Ca associated with a 0.903 increase in TyG index. Albumin partially mediated this relationship, accounting for approximately 21.74% of the effect of serum Ca on TyG index. The models demonstrated a consistent association across various adjustments for confounding variables.ConclusionsFindings suggest a mediation link between serum Ca and albumin and the risk of TyG index. The significance of albumin as a mediator deserves recognition and consideration.